ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP STRUKTUR MODAL PADA PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI PERIODE 2013-2016 - Delfia Amanda Flouresa, 15.05.62.0019; Wardjono, Wardjono (Students Journal of Accounting and Banking, 2018)
This research is aimed at testing and finding empirical proof influence of profitability, liquidity, sales growth, asset structure, size firm, and bussinees risk toward capital structure of Property and Real Estate sector Companies which listed in indonesian Stock exchange at period of 2013-2016.The sample is taken using purposive sampling technique. Data analysis technique used is multiple linear regression.This result of research show that variableProfitabilty, growth Sales, and asset structure have insignificant influence toward Capital Structure. Variable Size firm has positive significant influence toward Capital Structure. Variable Liquidity, and Bussiness risk haveÂ negative significant influence toward Capital Structure.Keywords : Capital Structure, Profitabilty, Liquidity, Sales Growth, Asset Structure, Size Firm, Bussiness Risk.